Hubungan Tingkat Kepatuhan Minum Obat Hipoglikemik Oral dengan Kadar Glukosa Darah pada Pasien Diabetes Melitus Tipe 2 - Wiwik Salistyaningsih Theresia Puspitawati Dwi Kurniawan Nugroho (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: Diabetes mellitus (DM) is a major health problem in the world and predicted a substantial increase of people with DM in the next years. In Public Health Center, the number of type 2 DM patient visits in 2010 increased compared to that in 2009 i.e 2.078 become 2.354 visits. The main goal of treatment of DM is keeping blood glucose contens within normal limits, an effort that can be done is to take oral hypoglycemic drugs (OHO) regularly.Aim: To know the correlation between the level of adherence to take OHO and blood glucose contens in type 2 DM patients in Umbulharjo II Public Health Center Yogyakarta.Method: This study used cross-sectional design with a population of 45 respondents, using a total sampling techniq.Results: The level of adherence to take OHO showed 31.1% proportion of non-adherent and 68.9% of adherent. Blood glucose contens showed 37.8% proportion of high and 62.2% of normal. From the analytical results obtained OR = 8.571 (CI95%: 2.045 to 35.923) meaning that non-adherent patients to take OHO have 8.6 times higher risk of blood increased glucose contens compared with patients who dutifully take OHO.Conclusion: There is a significant relationship between the level of adherence to take OHO and blood glucose contens in patients of type 2 DM.Keywords: the level of adherence to take OHO, blood glucose contens, type 2 DM.